(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The water in the Jakara River is a blend of domestic sewage from the north and central parts of the Kano metropolis and industrial effluent from the Bompai Industrial Estate. The wastewater in the river is the main source of irrigation water used by urban farmers in the city. Wastewater contaminated with heavy metals can be of public health concern when used for irrigation. The increasing concentration of several metals in soil and waters due to the Industrial Revolution has created an alarming situation for human life and aquatic biota. The study aims to determine the effect of season and location on the concentrations of Pb, Cd, Ni, Co, Cr and Hg in the irrigation water from the Jakara River. Water samples were collected from three locations monthly for 12 months from January to December 2022. The water samples were digested and subjected to heavy metals analysis using an atomic absorption spectrophotometer. Results of irrigation water analysis show that Pb and Cr are present in all the 36 samples taken during the study period. Co and Hg were not detected in all the samples taken during this period. Cd and Ni were not detected during September sampling, additionally, the concentrations of Pb and Cr detected in September were also the lowest. The highest concentrations were found in samples collected from Jaba and Kumantaka. It is only Pb concentration that exceeded the FAO/WHO permissible limit. Water samples collected in September at Airport Road possess the lowest heavy metals contamination...